The Effect of Packaging Redesign on Brand Image of Smart Mineral - Sonhaji Arif; Rizky Aditya Nugroho; Syahri Mu'min (GREENOMIKA, 2025)
This study aims to analyze the effect of packaging redesign on the brand image of Smart Mineral, with a specific focus on enhancing premium perception. The redesign process utilized the Design Thinking approach consisting of Empathize, Define , Ideate, Prototype, and Test stages. User evaluation was conducted on 20 respondents using a 1–5 Likert scale across five assessment aspects: premium perception, information clarity, visual cleanliness, design professionalism, and overall attractiveness. The results indicate that the redesign significantly improved all assessed aspects. Average premium perception increased from 3.10 to 4.45, while design professionalism increased most notably from 3.05 to 4.55. These findings confirm that visual packaging elements such as gradient blue color, minimalist water-drop icons, clean layout, and modern sans-serif typography strongly influence the formation of a premium brand image. This study also offers strategic recommendations for SMEs to utilize packaging design as a differentiation tool in competitive markets.